Prognostic significance of poorly differentiated cluster grading system in intestinal type gastric adenocarcinoma - Gurunluoglu, Semra; Samdanci, Emine; Kadir Arslan, Ahmet; Akpolat, Nusret; Sahin, Nurhan; Gokce, Hasan (Annals of Medical Research, 2021)
Aim: Gastric carcinoma is the fourth most common carcinoma worldwide. The relationships established between the tumor morphology and the prognosis have not been very effective until recent times. Poorly Differentiated Clusters (PDCs); are structures those can be easily identified in H&E sections. A new grading system based on PDC count has been studied in colorectal carcinoma; and found to be associated with prognosis. We have aimed to investigate this concept in gastric carcinoma.Material and Methods: Our study included 80 cases, consisting of 16 females and 64 males having gastric carcinoma with intestinal morphology. For each case; conventional grade, PDC grade and prognostic parameters to be applied in the study were determined, and statistically compared.Results: Significant discrepancy was found between the two grading systems. PDC tumor grades were statistically related to; median metastatic lymph node counts, metastatic lymph node ratios, lymph node stages (pN) and the presence of perineural invasion. Conclusion: In stomach carcinoma; PDC grading system was found to be related to a significant part of the expected parameters and may have a prognostic value.
Keywords: Poorly differentiated clusters; gastric carcinoma; histologic grade